The age-old problem of pollution, its role in endocrine disruption and the current analytical technologies that can be employed to monitor and assess waste water treatment plants - Olivier, Daniel Wilhelm (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.